2022
DOI: 10.3389/fcimb.2022.834653
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles From Paracoccidioides brasiliensis Can Induce the Expression of Fungal Virulence Traits In Vitro and Enhance Infection in Mice

Abstract: Extracellular vesicles (EVs) are cellular components involved in cargo delivery to the extracellular environment, including the fungal cell wall. Their importance in cell–cell communication, cell wall remodeling, and fungal virulence is starting to be better explored. In the human pathogenic Paracoccidioides spp., our group has pioneered the description of the EV secretome, carbohydrate cargo, surface oligosaccharide ligands, lipid, and RNA content. Presently, we studied the role of fungal EVs in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 66 publications
0
22
0
1
Order By: Relevance
“…M1-polarized macrophages exhibit a propensity for phagocytosis, microbial eradication, tumor cell elimination, and the induction of adaptive immunity. In vitro studies have shown that Aspergillus flavus, Trichoderma interrogans, and Paracoccidioides brasiliensis-derived EVs induce macrophage polarization toward the M1 phenotype, enhancing the clearance of microorganisms originating from the EVs’ source. ,, Our results highlighted the bioactivity of AF-derived EVs in effectively stimulating the upregulation of the inflammation level of RAW264.7 cells. Similarly, AF-derived EVs were found to modulate the inflammatory response of PMNs, as evidenced by increased mRNA expression of proinflammatory mediators, enhanced conidia phagocytosis, and improved conidia-killing ability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…M1-polarized macrophages exhibit a propensity for phagocytosis, microbial eradication, tumor cell elimination, and the induction of adaptive immunity. In vitro studies have shown that Aspergillus flavus, Trichoderma interrogans, and Paracoccidioides brasiliensis-derived EVs induce macrophage polarization toward the M1 phenotype, enhancing the clearance of microorganisms originating from the EVs’ source. ,, Our results highlighted the bioactivity of AF-derived EVs in effectively stimulating the upregulation of the inflammation level of RAW264.7 cells. Similarly, AF-derived EVs were found to modulate the inflammatory response of PMNs, as evidenced by increased mRNA expression of proinflammatory mediators, enhanced conidia phagocytosis, and improved conidia-killing ability.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of cell-derived EVs in Ophthalmology has been studied on multiple diseases, and the focus has mostly been on their regeneration function for neuro or specific component cells . Studies on EVs derived from Candida albicans, Dermatophyte Trichophyton, Cryptococcus, and others have revealed that the immunogenic components within these cargo materials impact host immune function. Due to their cell-free nature and the presence of multiple pathogen-associated molecular patterns (PAMPs), EVs possess the ability to induce robust and sustained immune responses. Pre-emptive application of fungal EVs to the host has shown to mitigate the lethality of fungal infections and reduce tissue destruction caused by the immune response of the host. , …”
mentioning
confidence: 99%
“…EVs play a fundamental role in various processes such as: pathogen adhesion and invasion, modulation of the immune response, in cell damage and death, as well as in the transmission of resistance and survival factors between pathogens (Table 1) (Figure 1). The inducing effect of EVs depends on factors such as the type of target cell [20], the species and even the strain in study [7,42], as well as the amount and time in which the vesicles interact [4].…”
Section: Extracellular Vesicles In Pathogenic Processesmentioning
confidence: 99%
“…Similar results have been reported through in vivo assays, where it was demonstrated that the interaction of EVs emitted by pathogenic organisms interacting with mice is related to greater cellular invasion. For example, exposing mice to EVs days before infection with the fungi S. brasilensis [23] or P. brasilensis [42] increased the fungal load in skin and lung lesions, respectively. On the other hand, the heart and blood of mice treated with EVs prior to infection with the protozoan T. cruzi, shown a higher parasite load compared to mice without exposure to EVs [36].…”
Section: Increased Adherence and Invasion Of Pathogensmentioning
confidence: 99%
See 1 more Smart Citation